2019
DOI: 10.3390/fluids4020098
|View full text |Cite
|
Sign up to set email alerts
|

Lubrication Approximation for Fluids with Shear-Dependent Viscosity

Abstract: We present dimensionally reduced Reynolds type equations for steady lubricating flows of incompressible non-Newtonian fluids with shear-dependent viscosity by employing a rigorous perturbation analysis on the governing equations of motion. Our analysis shows that, depending on the strength of the power-law character of the fluid, the novel equation can either present itself as a higher-order correction to the classical Reynolds equation or as a completely new nonlinear Reynolds type equation. Both equations ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…As a result, the load-carrying capacity of the journal bearing may increase as the frictional force decreases due to slip. From the modeling point of view, the power-law model is often used to express the non-Newtonian characteristics [26][27][28][29][30]. An interesting review was presented by Dang et al [31], who revealed that non-Newtonian lubricants demonstrated improved journal bearing performance when compared to Newtonian lubricants operating under specific conditions.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the load-carrying capacity of the journal bearing may increase as the frictional force decreases due to slip. From the modeling point of view, the power-law model is often used to express the non-Newtonian characteristics [26][27][28][29][30]. An interesting review was presented by Dang et al [31], who revealed that non-Newtonian lubricants demonstrated improved journal bearing performance when compared to Newtonian lubricants operating under specific conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Pereira, et al [19] rigorously derive the Reynolds lubrication approximation for steady flows of incompressible non-Newtonian fluids with shear dependent viscosity. They use a perturbation analysis and show that depending on the power-law character of the fluid, the derived equations can either be prescribed as a higher-order correction to the Reynolds equation or a new type of Reynolds equation for these non-linear fluids.…”
mentioning
confidence: 99%